2019 Mw 6.0 Mesetas (Colombia) Earthquake Sequence: Insights From Integrating Seismic and Morphostructural Observations. Issue 12 (2nd December 2022) - Poveda, Esteban; Pedraza, Patricia; Velandia, Francisco; Mayorga, Edwin; Plicka, Vladimír; Gallovič, František; Zahradník, Jiří
Abstract: The boundary between the Northern Andean block and the South American plate is a first‐order tectonic structure in Colombia with historically M > 7 earthquakes. However, details about individual sections of the system remain unknown. We illuminate the seismotectonic of the Algeciras fault by investigating an earthquake sequence that started on 24 December 2019. Using seismic networks at region, we estimate foreshocks and aftershocks focal mechanisms, local stress field, kinematic slip models of the largest events, and Coulomb stress changes. We integrate seismological and morphostructural observations to characterize source properties and reinterpret local faults. Two mainshocks (doublet of Mw 6.0 and 5.8) occurred within 16 min, rupturing just a few kilometers from each other. Discrimination of causative faults among the centroid moment‐tensor nodal planes is difficult because the focal zone is a complex tectonic environment. The focal mechanisms and the local stress field obtained are consistent with a regional NE trending dextral transpressive shear. The relocated aftershocks show a cluster with an L‐shaped pattern concentrated in a ∼7 × 7 km area. Our model defines the Algeciras fault with two structural styles for its northern termination. The NW part is characterized by a duplex‐style of right‐lateral strike‐slip with inner secondary faults of the same sense of movement, and the SE zone by a domino‐style system with inner minor faults of sinistral kinematics. The earthquake doublet is in the zone characterized by the duplex style. In contrast, the southern part of the aftershocks is located in the zone characterized by the domino style. Plain Language Summary: We studied the twin earthquakes (Mw 6.0 and 5.8) of 24 December 2019, and their sequence of aftershocks that occurred in the settlement of Mesetas, department of Meta, Colombia. The seismic activity is located 200 km south of the capital of the country in the foothills of the Eastern Cordillera in a region of high seismic potential between the Algeciras and Guaicáramo fault systems. To investigate the earthquake rupture, we used local and regional seismic waveforms to estimate seismic source properties of main events and its 17 aftershocks ( M > 4) through several methods, such as the analysis of location, focal mechanism, finite‐extent modeling of slip distribution on the assumed fault planes, and Coulomb stress transfer. Furthermore, we performed geologic and tectonic analyses, such as mapping the fault traces based on morphostructural analysis. We conclude that the Algeciras Fault System combines duplex and domino styles with dextral sense south of the Guaicáramo Fault System and defining the eastern boundary of the cordillera. Key Points: For the first time, an M ∼ 6 earthquake sequence is in‐depth analyzed in a focal zone, suggesting a transpressive stress regime The 2019 sequence and reinterpreted morphostructural data reveal recently activated faults Two mainshocks occurred as a doublet on nearly parallel faults oblique to the major Algeciras Fault System